Comparison between cage and pond production of Thai Climbing Perch (Anabas testudineus) and Tilapia (Oreochromis niloticus) under three management systems (Journal of the Bangladesh Agricultural University, 2011)
An experiment was conducted to compare production and economic performance of Thai Climbing Perch (Anabas testudineus) and Tilapia (Oreochromis niloticus) under three management systems. The nursed juveniles of Thai Climbing Perch (6.22 ± 0.15g) and Tilapia (22.52 ± 0.73g) were stocked at 50 Thai Climbing Perch per 1m3 cage and 50 Tilapia per 80m2 open pond (Caged Perch); 50 Tilapia per 1m3 cage and 50 Thai Climbing Perch per 80 m2 open pond (Caged Tilapia); and both 50 Thai Climbing Perch and 50 Tilapia per 80m2 pond (Mixed culture) as three treatments with three replicates for each. Pelleted feed (35% crude protein) was given twice daily (8.0 h and 16.0 h) at a rate of 10% body weight of Thai Climbing Perch for first month and 5% body weight of Thai Climbing Perch for rest of the culture period (90 days) to cages for the integrated cage-pond culture and to open ponds for the mixed culture. Among the measured water quality parameters transparency (cm), alkalinity (mg l-1), nitrite-nitrogen (mg l-1), and chlorophyll-a (μg l-1) were significantly different among the treatments. A total of 43 genera of phytoplankton and 16 genera of zooplankton were identified from the pond water. The mean abundance of total macro-benthic organisms was not significantly different (P>0.05). The mean survival rate of Thai Climbing Perch was high, ranging from 86.67% to 98.67%. Gross yield of Thai Climbing Perch was the highest in the Caged Perch. Survival of Tilapia was also high, ranging from 94.00% to 96.67%. The combined FCRs were 0.75, 0.77 and 0.85 in the Caged Perch, Mixed culture and Caged Tilapia systems, respectively. Economic analysis revealed that a significantly higher (P